(untitled) (Itinera, 2012)
The epigram of the Greek Anthology IX 400 has generated an age-old debate. The discussion is about its attribution to the Alexandrine poet Palladas – the last great exponent of the Hellenic civil poetry – and its dedication to the philosopher Hypatia. If we read the epigram in the context of Palladas’ poetics as well as in that of the Neoplatonic sources (in particular Synesius and Damascius) mentioning Hypatia, we are allowed to claim that this poem offers a precious evidence about the philosopher’s teachings and her political relevance between the end of the IV and the beginning of the V century A.D. The epigram, in fact, is to be considered one of the poems that Palladas dedicated to the debate on the ‘fair political practice’ that inflamed the Hellenic milieu. In relation to the betrayal of the Platonic political ideal by Themistius, the true philosopher Hypatia rises into the Eastern sky, as the earthly embodiment of the heavenly Virgin.